The efficacy and safety of anti-vascular endothelial growth factor combined with Ahmed glaucoma valve implantation in the treatment of neovascular glaucoma: a systematic review and meta-analysis - He, Chang-Zhu; Lu, Song-Jie; Zeng, Zhao-Jun; Liu, Jun-Qiao; Qiu, Qin; Xue, Fu-Li; He, Yu (Frontiers in Medicine, 2024)
Background The intraocular injections of anti-vascular endothelial growth factor (anti-VEGF) demonstrates significant efficacy in inhibiting the formation of ocular neovascularization in neovascular glaucoma (NVG). Ahmed glaucoma valve implantation (AGVI) is extensively employed for the management of diverse glaucoma types. Objective To further evaluate the efficacy and safety of anti-VEGF combined with AGVI in the treatment of neovascular glaucoma. Methods A thorough search for randomized controlled trials (RCTs) was conducted across eight databases: PubMed, EMBASE, the Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, SinoMed, and VIP. The search period was set from the inception of each database until March 2, 2024, to identify RCTs investigating the effectiveness and safety of combining AGVI with anti-VEGF therapy for NVG. We used the Cochrane Risk of Bias Assessment Tool to evaluate the quality of the literature and performed statistical analysis using Stata 15.0 software. Results Fourteen RCTs were included in this study. Compared with AGVI alone, the combination of anti-VEGF drugs and AGVI can reduce postoperative intraocular pressure (IOP) at 1 week [WMD = −4.03, 95% CI (−5.73, −2.34), p < 0.001], 1 month [WMD = −5.39, 95% CI (−7.05, −3.74), p < 0.001], 3 months [WMD = −6.59, 95% CI (−7.85, −5.32), p < 0.001], 6 months [WMD = −4.99, 95% CI (−9.56, −0.43), p = 0.032], and more than 12 months [WMD = −3.86, 95% CI (−6.82, −0.90), p = 0.011], with a higher Effective rate [RR = 1.27, 95% CI (1.18, 1.37), p < 0.001], decreased incidence of postoperative hyphema [RR = 0.24, 95% CI (0.15, 0.39), p < 0.001], reduced use of postoperative antiglaucoma medications [WMD = −0.48, 95% CI (−0.61, −0.35), p < 0.001], and decreased aqueous humor VEGF levels [SMD = −2.84, 95% CI (−4.37, −1.31), p < 0.001]. Conclusion In comparison to AGVI alone, the combination of AGVI with anti-VEGF therapy has better effects in reducing IOP at various time intervals, diminishing postoperative antiglaucoma medication requirements and reducing aqueous humor VEGF levels. Furthermore, it effectively minimizes the incidence of postoperative hyphema. Nevertheless, due to the variability in the quality of the trials included, further high-quality experiments will be required in the future to substantiate this conclusion. Systematic review registration PROSPERO, identifier CRD42024519862, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024519862.